Carbon Reduction Programs and Lower Income Households in Australian Cities. (2017) - Liu, Edgar; Judd, Bruce; Mataraarachchi, Sarath
Abstract: This paper presents preliminary findings of a recent research project on the barriers that lower-income households in four Australian cities – Sydney, Adelaide, Hobart, and Darwin – face in reducing their carbon consumption, and the impact of programs implemented by federal and state governments and support organisations to assist such reductions. Following a brief explanation of the methodology (policy reviews, focus group discussions with lower-income households, and interviews with support service providers and advocacy groups), it outlines issues that underlie the complexity of carbon reduction among lower income households. These include housing quality and tenure; health conditions; and user understanding and perspectives on low carbon living and environmental decision-making. This is followed by a review of the types of carbon reduction programs currently available to households living in different Australian jurisdictions. The paper will then reflect on focus group participants' views of their access to these programs, their perceived effectiveness in achieving genuine carbon reduction, and how these programs fit in (or not) to the less formal carbon reduction techniques already employed by lower income households. It also highlights the challenges and limitations support service providers and advocacy groups face in connecting lower-income households to carbon reduction programs. It concludes with a discussion of potential policy avenues to address the barriers to low carbon living and ensure the intended outcomes of these carbon reduction programs are met in the longer term for those on lower incomes.